Emerging Innovations and Clinical Perspectives in Dental Implantology: A Contemporary Review (Academia Journal of Medicine, 2026)
Dental implants have become a reliable and widely accepted treatment option for  replacing missing teeth. Continuous advancements in biomaterials, implant design, digital  technologies, and regenerative procedures have significantly enhanced the predictability and  long-term success of implant therapy. Modern developments such as surface modification  techniques, computer-guided implant placement, and biologically active coatings have  improved osseointegration and treatment outcomes. Furthermore, digital workflows and  advanced imaging techniques allow clinicians to plan and execute implant procedures with  greater accuracy. Despite these improvements, complications such as peri-implant diseases  and the need for long-term clinical evidence remain important concerns. This review  discusses contemporary advancements in dental implantology and highlights potential  future directions aimed at improving patient care and clinical success.
Keywords: Implant; Innovation; Digital Dentistry